2020
DOI: 10.1038/s41380-020-0649-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of depression-related behaviors by adiponectin AdipoR1 receptors in 5-HT neurons

Abstract: The adipocyte-derived hormone adiponectin has a broad spectrum of functions beyond metabolic control. We previously reported that adiponectin acts in the brain to regulate depression-related behaviors. However, its underlying neural substrates have not been identified. Here we show that adiponectin receptor 1 (AdipoR1) is expressed in the dorsal raphe nucleus (DRN) and colocalized with tryptophan hydroxylase 2 (TPH2), a marker of serotonin (5-HT) neurons. Selective deletion of AdipoR1 in 5-HT neurons induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 88 publications
1
31
0
Order By: Relevance
“…In particular the postpartum period is considered the time of greatest risk for women to develop MDD [41]. In order to address response of susceptibility in postpartum female mice, we applied a short term SCUS (3 days CUS), which is the usually used strategy to evaluate the susceptibility to stress [42,43]. Our findings demonstrated that female mice after parturition showed similar depression-like phenotypes to virgin females, which means the parturition stress alone cannot induce depression, while postpartum female mice showed enhanced susceptibility to SCUS induced depression-related behavior compared to virgin females, which reminds that 3 days stress may be the threshold of time window for stress induced depressive behaviors in PPD model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular the postpartum period is considered the time of greatest risk for women to develop MDD [41]. In order to address response of susceptibility in postpartum female mice, we applied a short term SCUS (3 days CUS), which is the usually used strategy to evaluate the susceptibility to stress [42,43]. Our findings demonstrated that female mice after parturition showed similar depression-like phenotypes to virgin females, which means the parturition stress alone cannot induce depression, while postpartum female mice showed enhanced susceptibility to SCUS induced depression-related behavior compared to virgin females, which reminds that 3 days stress may be the threshold of time window for stress induced depressive behaviors in PPD model.…”
Section: Discussionmentioning
confidence: 99%
“…The other group (control) was handled daily. In some experiments, an abbreviated (3 days) subthreshold chronic unpredictable stress was used to assess stress susceptibility in normal control and postpartum female mice [43].…”
Section: Postpartum Depression Modelmentioning
confidence: 99%
See 3 more Smart Citations